Enzymatic cleavage of a bacterial genome at a 10-base-pair recognition site. - Weil, M D (1989)
The circular genome of Staphylococcus aureus was cut into two fragments by a simple enzymatic method that cleaves a 10-base-pair site. The recognition sequence, A-T-C-G-mA decreases T-C-G-mA-T, was created by the combined use of the methylase M.Cla I (A-T-C-G-mA-T) and the restriction endonuclease Dpn I (G-mA decreases T-C). This technique is insensitive to CpG methylation and in human DNA is predicted to produce fragments that, on average, are greater than five million base pairs. The ability to create such long pieces of DNA should facilitate mapping of large, complex chromosomes.